2016
DOI: 10.1016/j.ihj.2015.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous coronary artery dissection: Case series and review of literature

Abstract: The awareness of SCAD is important for all clinicians involved in STEMI care. A prompt suspicion can avoid administration of thrombolytic therapy. Early coronary angiography will provide an accurate diagnosis and help in deciding appropriate therapy. Percutaneous intervention can be challenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…A recent study with 168 patients with SCAD revealed that only 26.1% of patients presented with ST-segment elevation, and 3.6% had ventricular fibrillation or ventricular tachycardia [4] . The LAD was found to be the most prevailing site of SCAD, as in our patient [2,6,7] .…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…A recent study with 168 patients with SCAD revealed that only 26.1% of patients presented with ST-segment elevation, and 3.6% had ventricular fibrillation or ventricular tachycardia [4] . The LAD was found to be the most prevailing site of SCAD, as in our patient [2,6,7] .…”
Section: Discussionmentioning
confidence: 57%
“…SCAD is a spontaneous tear of the inner layer in the coronary artery, creating a false lumen between the inner and central layer. This results in decreased coronary blood flow leading to acute coronary syndrome (ACS) [1,2] . The first reported case of SCAD was in 1931 during an autopsy in a 42-year-old woman.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The long-term prognosis is generally good at 95% after a follow-up of 2 years [ 36 ]. Several authors reported excellent long-term follow-up in patients who were managed conservatively [ 16 , 37 41 ].…”
Section: Discussionmentioning
confidence: 99%